2005
DOI: 10.1128/mcb.25.18.8097-8107.2005
|View full text |Cite
|
Sign up to set email alerts
|

RUNX3 Suppresses Gastric Epithelial Cell Growth by Inducing p21WAF1/Cip1 Expression in Cooperation with Transforming Growth Factor β-Activated SMAD

Abstract: RUNX3 has been suggested to be a tumor suppressor of gastric cancer. The gastric mucosa of the Runx3-null mouse develops hyperplasia due to enhanced proliferation and suppressed apoptosis accompanied by a decreased sensitivity to transforming growth factor ␤1 (TGF-␤1). It is known that TGF-␤1 induces cell growth arrest by activating CDKN1A (p21 WAF1/Cip1 ), which encodes a cyclin-dependent kinase inhibitor, and this signaling cascade is considered to be a tumor suppressor pathway. However, the lineage-specific… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
151
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 178 publications
(158 citation statements)
references
References 45 publications
(46 reference statements)
7
151
0
Order By: Relevance
“…Earlier shown to bind directly to TGF-b signaling effector SMAD3 for synergistic induction of Immunoglobulin germline C a promoter (Shi and Stavnezer, 1998; Hanai et al, 1999) during Immunoglogulin A class switching, RUNX3 is now also known to have a function in TGF-b-induced growth inhibition. After stimulation by TGF-b cytokines, RUNX3 cooperates with SMAD proteins to directly upregulate transcription of the proapoptotic gene Bim1 and increase expression of the cyclin-dependent kinase inhibitor p21 WAF1 in gastric cancer cells (Chi et al, 2005;Yano et al, 2006). Moreover, the ability of RUNX3 to target SMADs to distinct nuclear foci on stimulation by TGF-b further strengthens the case for RUNX3 as a regulator of the TGF-b signaling pathway (Zaidi et al, 2002).…”
Section: Molecular Mechanisms That Underlie Runx3's Anti-tumor Propermentioning
confidence: 77%
See 1 more Smart Citation
“…Earlier shown to bind directly to TGF-b signaling effector SMAD3 for synergistic induction of Immunoglobulin germline C a promoter (Shi and Stavnezer, 1998; Hanai et al, 1999) during Immunoglogulin A class switching, RUNX3 is now also known to have a function in TGF-b-induced growth inhibition. After stimulation by TGF-b cytokines, RUNX3 cooperates with SMAD proteins to directly upregulate transcription of the proapoptotic gene Bim1 and increase expression of the cyclin-dependent kinase inhibitor p21 WAF1 in gastric cancer cells (Chi et al, 2005;Yano et al, 2006). Moreover, the ability of RUNX3 to target SMADs to distinct nuclear foci on stimulation by TGF-b further strengthens the case for RUNX3 as a regulator of the TGF-b signaling pathway (Zaidi et al, 2002).…”
Section: Molecular Mechanisms That Underlie Runx3's Anti-tumor Propermentioning
confidence: 77%
“…This seems to stem from multiple defects in its protein properties. The R122C mutant has reduced affinity for DNA with the consensus RUNX-binding site; it is also less efficient in binding SMADs (Chi et al, 2005). The combination of these defects results in impaired participation in TGF-b signaling, as seen by reduced activation of p21 WAF1 promoter during TGF-b stimulation (Chi et al, 2005).…”
Section: Molecular Mechanisms That Underlie Runx3's Anti-tumor Propermentioning
confidence: 99%
“…RUNX3 has been shown to contribute to tumor suppressor activity as a component of the TGF- tumor suppressor pathway 9 through the attenuation of cell growth with a CDK inhibitor 13 , induction of apoptosis 15 , and inhibition of angiogenesis 16 and metastasis 31 in gastric cancers. Here, we showed that RUNX3 also exerts its tumor functions as a tumor suppressor under the TGF--signalling pathway 9 .…”
Section: Discussionmentioning
confidence: 99%
“…For example, RUNX3 (a transcription factor of the Runt family) has been shown to be required for TGFβ-induced CDKN1A expression 108 and cell-cycle arrest 109 , whereas Notch signalling has been shown to be required for TGFβ-induced epithelial to mesenchymal transition 110 . Interestingly, KLF4 is also linked to these pathways.…”
Section: Linking Opposing Forces In Cancermentioning
confidence: 99%